Pelatihan Branding pada UMKM Desa Ngrimbi Melalui Pendekatan Mentoring - Muhammad Fahrezi Ramadhani; Raden Johnny Hadi Raharjo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a role in maintaining the national economy.  Seeing the potential of MSMEs which can support the economy, MSMEs are one of the businesses that are currently growing a lot. One of the strategies that can be carried out by SMEs is to optimize branding. Ngrimbi Village is one of the villages in Jombang Regency which has MSMEs with a total of around 20 MSMEs. However, most MSMEs in Ngrimbi Village do not have the skills to do branding. So that in supporting the development of MSMEs, it is necessary to have training in branding skills. This training was carried out by KKN Tematik UPN “Veteran” Jawa Timur students with a Mentoring approach. Mentoring activities are carried out in two sessions, namely the presentation and mentoring sections. This training aims to make MSME actors have branding skills in developing their businesses. The research method used is a qualitative approach with data collection techniques in the form of observation and interviews. From the results of the study it was found that by using the mentoring method, MSME actors can understand how to do branding. MSME actors gain knowledge and skills in branding.